Similar clinical outcomes with transcatheter aortic valve implantation and surgical aortic valve replacement in octogenarians with aortic stenosis - Kolar, Tadeja; Lakič, Nikola; Kotnik, Aleša; Štubljar, David; Fras, Zlatko; Bunc, Matjaž (Frontiers in Cardiovascular Medicine, 2022)
Background: Transcatheter aortic valve implantation (TAVI) is the preferred treatment option for severe aortic stenosis in the elderly and in patients with comorbidities. We sought to compare outcomes after TAVI and surgical aortic valve replacement (SAVR) in octogenarians. Methods: In this retrospective cohort study conducted at our tertiary center, clinical data were gathered before and after TAVI and SAVR procedures performed from January 2013 to May 2019; follow-up completed in March 2021. The primary outcome was 1-year mortality. Patients were stratified according to Society of Thoracic Surgeons (STS) score and procedure type. Results: Of 542 patients who matched the inclusion criteria, 273 underwent TAVI and 269 SAVR. TAVI patients were older (85.8±3.0 vs. 82.2±2.2 years; P<0.001) and had a higher mean STS score (5.0±4.0 vs. 2.8±1.3; P<0.001) and EuroSCORE II (5.3±4.1 vs. 2.8±6.0; P<0.001). Rates of postoperative permanent pacemaker insertion (15.0% vs. 9.3%; P=0.040) and paravalvular leak (9.9% vs. 0.8%; P<0.001) were higher and acute kidney injury lower (8.8% vs. 32.7%; P<0.001) after TAVI, with no difference between treatment groups for major bleeding (11.0% vs. 6.7%; P=0.130) or 30-day mortality (5.5% vs. 3.7%; P=0.315). A statistically significant difference was found between TAVI and SAVR in low- and intermediate-risk groups when it came to occurrence of paravalvular leak, acute kidney injury, and new onset AF (all P<0.001). Conclusion: This analysis of an octogenarian “real-life” population undergoing TAVI or SAVR (with a biological valve) showed similar outcomes regarding clinical endpoints in low- and medium-risk (STS score) groups.